SWOT Analysis and Strengthening Socialization for BUMDes Tetus, Kuanheum Village, West Kupang - Paul Alfred Yamba Kodi; Delviana B. Nulle; Maria Stefania Conny Kwen; Vergilius Manehat; Claudia Meilin Putri Lau; Ignasius Rendino Lima; Tarsisius Andriano Galung; Arsinius Tanggu; Auria Sandra Jelia Delima Ros Reis; Andriana Evangida Usfal; Theresia Ekawati Indriani; Klaudia Malon; Anna Monica Triana; Mathilde Camelia Raga; Johanes Serafim Teku; Aplonia Nelci Ke Lomi (Asian Journal of Community Services, 2022)
Village-Owned Enterprises (BUMDes) is one of the businesses that are expected to be able to revive the economy of villages in Indonesia. In supporting one of the Ministry of Village, Development, of Disadvantages Regions and Transmigration programs, the Community service team (KKNT-PPM) Widya Mandira Catholic University (UNWIRA) Kupang did the analysis and strengthening socialization for BUMDes in Kuanheum Village, West Kupang District, Kupang Regency. In the study, there were many weaknesses and threats that the management must know of BUMDes Tetus in Kuanheum Village. There are also advantages of the BUMDes and the village and opportunities that could be optimized for the village's progress. As a direct effort, the UNWIRA KKNT-PPM team carried out socialization, including facilitated discussions with various parties that could help the development of the village economy. This program is expected to be sustained and monitored to produce optimal results for the better development of Kuanheum Village